Comparative energy, exergy and exergo-economic analysis of solar driven supercritical carbon dioxide power and hydrogen generation cycle. (19th February 2020) - Abid, Muhammad; Khan, Muhammad Sajid; Ratlamwala, Tahir Abdul Hussain
Abstract: Parabolic dish solar collector system has capability to gain higher efficiency by converting solar radiations to thermal heat due to its higher concentration ratio. This paper examines the exergo-economic analysis, net work and hydrogen production rate by integrating the parabolic dish solar collector with two high temperature supercritical carbon dioxide (s-CO2 ) recompression Brayton cycles. Pressurized water (H2 O) is used as a working fluid in the solar collector loop. The various input parameters (direct normal irradiance, ambient temperature, inlet temperature, turbine inlet temperature and minimum cycle temperature) are varied to analyze the effect on net power output, hydrogen production rate, integrated system energetic and exergetic efficiencies. The simulations has been carried out using engineering equation solver (EES). The outputs demonstrate that the net power output of the integrated reheat recompression s-CO2 Brayton system is 3177 kW, whereas, without reheat integrated system has almost 1800 kW net work output. The overall energetic and exergetic efficiencies of former system is 30.37% and 32.7%, respectively and almost 11.6% higher than the later system. The hydrogen production rate of the solarized reheat and without reheat integrated systems is 0.0125 g/sec and 0.007 g/sec, accordingly and it increases with rise in direct normal irradiance and ambient temperature. The receiver has the highest exergy destruction rate (nearly 44%) among the system components. The levelized electricity cost (LEC) of 0.2831 $/kWh with payback period of 9.5 years has proved the economic feasibility of the system design. The increase in plant life from 10 to 32 years with 8% interest rate will decrease the LEC from (0.434-0.266) $/kWh. Recuperators have more potential for improvement and their cost rate of exergy is higher as compared to the other components. Highlights: Two different Brayton cycles with and without reheat are being analyzed in this paper. The HTF used is pressurized water for solar collector and s-CO2 for Brayton cycles. The reheat Brayton cycle has 11.6% higher efficiency as compared to its counterpart. The reduction in LEC proves the economic feasibility of the system design.